The culture of interpretation Christian faith and the postmodern world - Lundin, Roger (Grand Rapids, MI Eerdmans, 1993)
Includes bibliographical references and index.
Keywords: Deconstruction; Postmodernism -- religious aspects -- Christianity; Christianity and culture -- history of contemporary events